POPULASI DAN SERANGAN HAMA Thrips spp. (THYSANOPTERA: THRIPIDAE) PADA BEBERAPA VARIETAS TANAMAN KRISAN DI KELURAHAN KAKASKASEN II KECAMATAN TOMOHON UTARA - Andre V.H. Najoan; Julie M.E. Mamahit; Betsy A.N. Pinaria (Universitas Sam Ratulangi, 2017)
SUMMARY Thrips spp. is an important pest that one of the obstacles in the cultivation of chrysanthemum. Research using plant propagation greenhouse flowers are located in the Village Kakaskasen II, North Tomohon sub district and in the Laboratory of Entomology and Plant Pests Agricultural Faculty UNSRAT Manado. The study was conducted by observing the population of Thrips spp. in some varieties of chrysanthemum plants, namely (1) varieties Solinda Pelangi, (2) Kulo varieties (white Lokon) and (3) varieties Puspita Nusantara. Observations pest populations conducted in five sub-plots by taking seven samples of chrysanthemum on each sub-plot, then the plants were taken in quotation strands interest to observe whether or not found Thrips pest. Thrips both nymphs and imago found in chrysanthemum flowers strands are collected in a bottle collection that already contains 70% alcohol and then calculated the amount. Thrips pest collected then taken to the Laboratory of Entomology and Plant Pests Faculty of Agriculture, University of Sam Ratulangi to be observed. Observations Thrips pest populations spp. performed a total of four (4) times with a time interval of the chrysanthemum plant once a week on the age of 8 weeks after planting (mst), 9 mst, 10 and 11 mst mst. Observations made on the amount of interest stricken old plants 11 weeks after planting to record and count the number of affected plants. Criteria interest stricken characterized by the presence of symptoms of pests Thrips spp. and or presence of nymphs / imago on the sample of interest. The results showed that pest populations Thrips spp. the three highest chrysanthemum varieties found in Kulo varieties, reaching an average of 38.5, then Solinda Pelangi 21.5 varieties and varieties Puspita Nusantara 12.1. Pest populations of Thrips spp. at the level of plant age turns on old plants 11 weeks after planting (mst) has a population of Thrips spp. The highest, reaching an average of 32.3, then aged 10 mst 32.0, age 9 mst 20.2 mst, and age 8 mst 14.9. Turns infected plants vary between varieties. A total of 64 flowers of each variety turns highest percentage of infected plants was found in 81.25% Kulo 52 varieties of flowers attacked, then varieties Solinda Pelangi 64.06% 41 flower attacked and Puspita Nusantara 43.75% interest 28 attacked. Keywords: Population, attack Hama, Chrysanthemum.